Pengaruh Net Income, Cash Flow from Operations, dan Company Size Terhadap Dividend Policy - Elis Natasya; Zulkarnain Zulkarnain (Winter Journal: IMWI Student Research Journal, 2022)
This study was conducted to determine the effect of net income, cash flow from operations, and company size on dividend policy on basic and chemical sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2012-2016. The test was carried out using multiplle linear regression test with SPSS version 21. The study was conducted on 35 observations from annual reports of 7 companies samples from the selection by purposive sampling. Independent net income (X1), cash flow from operations (X2), and company size (X3) to dividend policy (Y). Companies that earn profits do not directly distribute dividends but are used for reinvestment. Companies with a limited amount of cash can distribute dividends in the from of stock dividends and large companies do not always distribute dividends because the economy is not stable so that the management of company funds is not effective. This situation makes the company prioritize the company’s growth.